2023
DOI: 10.1186/s12888-023-04659-2
|View full text |Cite
|
Sign up to set email alerts
|

Valproate-related neutropenia and lithium-related leukocytosis in patients treated with clozapine: a retrospective cohort study

Abstract: Background Neutropenia is a noteworthy side effect of clozapine, which might warrant this drugs’ discontinuance for safety. Studies have revealed that the risk of neutropenia increases with concurrent administration of valproate, but the evidence was limited. Conversely, lithium may have an ameliorating effect on clozapine-induced neutropenia. This study explored the effects of valproate and lithium on white blood cell counts in patients treated with clozapine. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Considering the temporal association between the onset of neutropenia and COVID‐19 infection in this scenario, ostensibly COVID‐19 was suggested to be a key factor. The true causality of neutropenia in this scenario was clouded by the presence of confounding factors such as clozapine, sodium valproate, and olanzapine; medications known to be associated with neutropenia and the inherent known increased risk of CAN in the initial period following clozapine commencement 5,23,38,39 . Moreover, a cohort study has suggested that concurrent use of sodium valproate is a significant additional risk factor for CAN (up to 5‐fold higher compared to clozapine alone) 39 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering the temporal association between the onset of neutropenia and COVID‐19 infection in this scenario, ostensibly COVID‐19 was suggested to be a key factor. The true causality of neutropenia in this scenario was clouded by the presence of confounding factors such as clozapine, sodium valproate, and olanzapine; medications known to be associated with neutropenia and the inherent known increased risk of CAN in the initial period following clozapine commencement 5,23,38,39 . Moreover, a cohort study has suggested that concurrent use of sodium valproate is a significant additional risk factor for CAN (up to 5‐fold higher compared to clozapine alone) 39 .…”
Section: Discussionmentioning
confidence: 99%
“…The true causality of neutropenia in this scenario was clouded by the presence of confounding factors such as clozapine, sodium valproate, and olanzapine; medications known to be associated with neutropenia and the inherent known increased risk of CAN in the initial period following clozapine commencement. 5,23,38,39 Moreover, a cohort study has suggested that concurrent use of sodium valproate is a significant additional risk factor for CAN (up to 5-fold higher compared to clozapine alone). 39 We were also unable to confirm if the improvements in WCC and ANC counts occurred purely because of lithium (immunomodulating and/or neutrophilic effects), temporary cessation of clozapine, or natural recovery from COVID-19 infection.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Though all these medications individually can cause agranulocytosis, the simultaneous use of all 3 drugs plus a haldol decanoate injection may explain the patient's absolute neutropenia count of zero. Concurrent valproate use and older age are associated with the development of neutropenia in patients treated with clozapine [10].…”
Section: Discussionmentioning
confidence: 99%
“…No association of the use of lithium carbonate with the risk of hematopoietic leukopenia was represented by the analyses with the data of 2453 clozapine users (Table 3 ). A retrospective cohort study using the medical record from a tertiary psychiatric hospital in Taiwan reported that neutropenia did not occur in 45 patients receiving clozapine and lithium, and that it developed in 20 (2.9%) out of 700 lithium-untreated clozapine users [ 28 ]. Our study used a spontaneous reporting database, and analyzed 530 patients exposed to clozapine and lithium carbonate.…”
Section: Discussionmentioning
confidence: 99%